Philon und die Philologen - Wyss, Beatrice (Biblische Notizen, 2011)
Alexandria is supposed to be the city of education and scientific development. This paper first tries to decide Alexandrias intellectual milieu in the first century CE by means of a prosopographical investigation resulting in uncovering among the intellectuals the importance played by philologists (grammatikoi). Having described the subject and its topics, I will present Philo’s mostly neutral treatment of it. Last I will show how he adapts philological methods and patterns in his exegetical work. Philo uses them without hesitation if they fit his exegetical purposes. An exceptional passage in De sacrificiis shows structural resemblance with Julius Pollux´ onomasticon.